ANALISIS KONTRASTIF DALAM PENERJEMAHAN ‘SIGHTSEEING’ - NUNING YUDHI PRASETYANI (Unipdu Jombang, 2012)
Nuning Yudhi Prasetyani Universitas Pesantren Tinggi Darul Ulum Jombang ningdibyo@gmail.com Abstract Contrastive analysis is a method that can be used to overcome the problem of translation. Contrastive analysis is defined as a sub-discipline of linguistics on contrasting two languages ​​or more (or a sub-system of the language) to determine the similarities and differences between two languages. Nababan (1997:8) explains that there are two kinds of contrastive studies, the theoretical and applied. Theoretical contrastive study examines in depth the differences and similarities between the two languages ​​or more to find a certain category or not in language A or language B, whereas applied contrastive study is part of a study of applied linguistics. By taking the results of the study of theoretical contrastive studies, this study is looking for a framework to compare languages ​​and focus on specific information for specific purposes, for example for language teaching, bilingualism analysis, and translation. Key words: contrastive analysis, translation, bilingualism analysis Abstrak Analisis kontrastif adalah metode yang dapat digunakan untuk mengatasi permasalahan dalam penerjemahan. Analisis kontrastif didefinisikan sebagai suatu disiplin sub-linguistik pada membandingkan dua bahasa (sistem sub-bahasa) untuk menentukan persamaan dan perbedaan antara dua bahasa tersebut. Nababan (1997:8) menjelaskan bahwa ada dua macam penelitian kontrastif, yakni analisis kontrastif teoritis dan terapan. Analisis kontrastif teoritis meneliti secara mendalam perbedaan dan persamaan antara dua bahasa atau lebih untuk menemukan kategori tertentu dalam bahasa A atau bahasa B, sedangkan penelitian kontrastif terapan merupakan bagian dari studi linguistik terapan. Melalui hasil analisis kontrastif teoritis, penelitian ini bertujuan untuk membandingkan dua bahasa yang fokus pada informasi spesifik untuk tujuan tertentu, misalnya untuk pengajaran bahasa, analisis bilingualisme, dan penerjemahan. Kata kunci: analisis kontrastif, terjemahan, analisis bilingualisme